Effect of Use of Information Technology, Accounting Information Systems, Internal Control Systems And Competence For Village Fund Management Accountability - Friyani, Rita; Yudi; Nurhayani; Faruk, Ahmad; Savitri, Riftiyanti; Furnawati, Raudhah (Archives of Business Research, 2023)
The aim of this research is to see the influence of the use of Information Technology, Accounting Information Systems, Internal Control Systems and Competence on the Accountability of Village Fund Management in Jambi District outside the city. The population in this research is the government village in Jambi Luar Kota District, Muaro Jambi Regency, which consists of 19 villages and 1 sub-district. Purposive sampling technique was used in sampling. Each village was selected by 3 respondents who were related to village financial management, namely the Village Head, Village Secretary and Head of Finance. The number of respondents in this study was 57 respondents. The data analysis method used is multiple linear regression using the SPSS version 24 software program.